152 Circulating serum extracellular matrix degradation enzyme Cathepsin S predicts mortality and improves risk stratification over the grace score in patients with non-ST elevation acute coronary syndromes. (May 2019) - Vlachogiannis, Nikolaos; Sopova, Kateryna; Georgiopoulos, Georgios; Mueller-Hennessen, Matthias; Sachse, Marco; Bakogiannis, Constantinos; Biener, Moritz; Vafaie, Mehrshad; Gatsiou, Aikaterini; Zaman, Azfar; Katus, Hugo; Spyridopoulos, Ioakim; et al.
Abstract : Introduction: Blood-based biomarkers may be useful in the identification of residual risk for death or acute myocardial infarction (AMI) in patients with a previous acute coronary syndrome. Cathepsin S (CTSS) is a lysosomal cysteine protease with potent elastolytic and collagenolytic activity, which plays an important role in cardiovascular disease through extracellular matrix degradation, vasa vasorum development and atherosclerotic plaque rupture. The aim of the present study was to determine the prognostic and reclassification value of baseline circulating levels of CTSS after adjustment for the Global Registry of Acute Coronary Events (GRACE) score, which is widely recommended for risk stratification in non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Methods: CTSS was measured in blood samples collected from 1, 129 consecutive patients with adjudicated NSTE-ACS presenting at an acute chest pain unit for evaluation of a possible acute coronary syndrome. Cardiovascular (CV) death and a composite of all-cause mortality and AMI were evaluated as the primary and secondary endpoints of the study, respectively. The additive prognostic value of CTSS over the GRACE score was estimated by the Net Reclassification Index (NRI) that examines the net upward and downward reclassification into correct pre-defined risk categories. Results: After a median follow-up of 21 months, 101 (8.95%) deaths were reported, of which 63 (5.6%) were of cardiac origin. The combined endpoint occurred in 176 (15.6%) patients. Patients with CTSS in the highest tertile presented the greatest risk for all-cause mortality (HR=1.84 for highest versus lowest tertile of CTSS distribution, 95% CI 1.1–3.08, P=0.02) and CV death (HR=2.5 for highest versus lowest tertile of CTSS distribution, 95% CI 1.24–5.05, P=0.011) after adjustment for age, gender, diabetes mellitus, hs-cTnT, hsCRP, revascularization and index diagnosis. Similarly, CTSS was associated with increased risk of cardiovascular death after adjusting for the GRACE Score (adjusted HR for highest versus lowest tertile of CTSS distribution=2.34, 95% CI 1.18–4.64, P=0.015). Further, CTSS predicted the combined endpoint of all-cause death or non-fatal MI independently of the GRACE Score (adjusted HR for highest versus lowest tertile of CTSS distribution=1.67, 95% CI 1.15–2.42, P=0.007). When CTSS was added over the GRACE Score, it conferred significant reclassification value for CV death (NRI=21.4%, P=0.008). Similarly, CTSS correctly reclassified risk for all-cause death or non-fatal MI (P=0.006) in 15.9% of the population. Conclusion: Circulating CTSS predicts mortality and improves risk stratification of patients with NSTE-ACS over the GRACE score recommended by clinical guidelines. The clinical application of CTSS as a novel biomarker in NSTE-ACS should be further explored and validated. Conflict of Interest: none